« Regarder le corps » dans la mythologie japonaise : tabou ou vertu ? - Ignacio Quiros (Itinéraires, 2011)
In the Kojiki and the Nihon-shoki, mythological records of ancient Japan, we can find many references to nudity. Naked body is often exposed to the eye, and depending on the episode, this association nudity-look is at the root of a wide range of reactions, from fascination to shame, from laughter to submission. Sometimes taboo, sometimes virtue, this relationship between nudity and look needs to be clarified, in order to better understand the body’s conception particular to these texts and to ancient Japanese culture.